Android Animation Application for Malaysian Natural Herbal Medicine - Ahmad Zaki, Nursyazwani; Hamid, Hashima (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: The development of Android animated applications for the Malaysian natural Herbal Medicine is an initiative taken to enhanced for animation application focus on traditional treatment using natural herbal medicine by indigenous Temuan. The existing approach is by verbally from their ancestors and not documented. This shows a lack of lost and not complete information. Therefore, this study proposed developing an animation application focused on Malaysia Natural Herbal Medicine for first aid treatment such as swollen, fracture and wound injuries. The objective of this study is designing an animated application for people of herbal medicine. Secondly, is to develop an animated application for Orang Asli herbal medicine. Lastly, is to test the functional reliability level of the Orang Asli Herbal medical animation application towards target users. This animation application has three subtopics which are the swollen treatment, fracture treatment and wound treatment. Developers have included animated videos and a description of their treatment via audio to attract users. The animation application was developed based on the ADDIE Model and the testing was implemented with the target user, the native tribe of Temuan. Assessment is carried out based on the questionnaire content design and multimedia design. The test results show that the application is able to improve herbal medicine as a method of initiative to the maintenance of orang Asli community entities especially in the medical field. The development of an effective animated application can help to improve consumer knowledge on the herbal medicine of this orang Asli. As such, the Android animation application for the Malaysian Orang Asli herbal medicine is able to give a positive impact on the availability of interactive designs that will meet the needs of consumers. Keywords: Android apps, Indegeneous medicine, Herbal Medicine, Animation